2018
DOI: 10.3389/fimmu.2018.02288
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Induces the Accumulation of Lung Mast Cells During Influenza Infection

Abstract: Mast cells release disease-causing mediators and accumulate in the lung of asthmatics. The most common cause of exacerbations of asthma is respiratory virus infections such as influenza. Recently, we demonstrated that influenza infection in mice triggers the recruitment of mast cell progenitors to the lung. This process starts early after infection and leads to the accumulation of mast cells. Previous studies showed that an adaptive immune response was required to trigger the recruitment of mast cell progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…When the controls were subgrouped according to their self‐reported health issues, two of the four control subjects with the highest MCp frequency reported respiratory problems (none of the controls were treated with inhaled corticosteroids). We recently found that during acute influenza infection in mice, innate immunity triggers the recruitment of MCp to the lung to a similar extent as allergic inflammation . The individuals included in our study had to be free from cold symptoms 2 weeks prior to the clinic visit.…”
Section: Discussionmentioning
confidence: 99%
“…When the controls were subgrouped according to their self‐reported health issues, two of the four control subjects with the highest MCp frequency reported respiratory problems (none of the controls were treated with inhaled corticosteroids). We recently found that during acute influenza infection in mice, innate immunity triggers the recruitment of MCp to the lung to a similar extent as allergic inflammation . The individuals included in our study had to be free from cold symptoms 2 weeks prior to the clinic visit.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, we demonstrated that influenza infection in mice induced the recruitment of MCps to the lung, which later gave rise to mast cells with intermediate expression of integrin β7 (immature/induced) and even later increased the number of mature mast cells with low expression of integrin β7 (38). While the recruitment of MCps induced by allergic lung inflammation was dependent on an adaptive immune response (54, 55), the influenza-induced MCp recruitment to the lung was due to the induction of innate immune responses (60). As respiratory infections commonly cause exacerbations of asthma symptoms, we think it is intriguing that influenza infections induces mast cell accumulation in the mouse lung.…”
Section: Mast Cell Accumulation In the Lung And The Mechanisms Behindmentioning
confidence: 99%
“…In vivo , TLR4-mediated mast cell activation was demonstrated to enhance eosinophilia and cytokine release in an OVA-model of allergic airway inflammation using mast cell-deficient (Kit W / Wv ) mice and reconstitution experiments (127). Furthermore, intranasal administrations of poly I:C expand the number of lung MCps in a TLR3-dependent fashion (60). To summarize, the activation of pattern recognition receptors may directly or indirectly induce or modulate mast cell responses in the allergic lung.…”
Section: Ige-independent Activation Of Mast Cells In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, poly(I:C)-activated upregulation of TLR3 expression was also demonstrated in murine bone marrowderived cultured MCs (BMMCs), though only at the mRNA level [31]. Furthermore, poly(I:C) stimulated a six-fold increase in the total number of lung MCs via TLR3 [49].…”
Section: Discussionmentioning
confidence: 96%